Sense of place and place attachment in tourism - Chen, Ning Chris; Prayag, Girish; Hall, Colin Michael 1961- (Routledge focus on tourism and hospitality, 2021)
"Place is integral to tourism. In tourism, almost all issues can ultimately be traced back to human-place interactions and human-place relationships. Sense of place, also referred to as place attachment, topophilia, and community sentiment, has received significant attention in tourism studies because it both contributes to, and is affected by, tourism. This book, written by notable authors in the field, examines sense of place and place attachment in terms of a typology of sense of place/place attachment that includes genealogical/historical, narrative/cultural, economic, ideological, cosmological, and dynamic elements. Dimensions of place attachment such as place identity, place dependence, and affective attachment, are discussed as well as place marketing, place making, and destination management. Complete with a range of illustrative international cases and examples ranging from Santa Claus to the importance of place in indigenous and traditional cultures, this book represents a substantial addition to knowledge on the inseparable relationship between tourism and place and will be of great interest to all upper-level students and researchers of Tourism"--